World communication report : the media and the challenges of the new technologies - Maherzi, Lotfi (Unesco ParisFR, 1997)
Focuses on the convergence between information technology, information and communication and their applications in the various media (written press, news agencies, radio and television) and provides statistics on the changes observed in this field. Highlights the major problems connected with the development of new information and communication technologies, such as the regulation of networks, media attitudes to violence and access of women to the media.